Measurement and modeling of race and health in Brazil: continuing the discussion - Margaret T. Hicken
Recent reviews have discussed the conceptualization of race in health studies in Brazil. This review further documents and discusses specific measurement and modeling issues with regard to race and how this can impact result interpretation. Three scientific databases were used to search the literature on race and three health outcomes. The search yielded 38 empirical studies on birth outcomes, self-rated health, and weight. Results suggest that, while there are racial patterns in the overall literature, conceptual and methodological challenges can be addressed to clarify the ways in which racial group membership is linked to health.